2016
DOI: 10.1002/jbm.b.33757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of 2,3‐dimercaptosuccinic acid‐modified Fe2O3nanoparticles on intercalated discs in engineered cardiac tissues

Abstract: Although iron oxide nanoparticles (IRONs) were applied in clinical magnetic resonance imaging in vivo and magnetic tissue engineering in vitro widely, the underlying effects of IRONs on the development of cardiomyocytes especially the intercellular junctions, intercalated discs (IDs), remain an unknown issue. Given the critical role of threedimensional (3D) engineered cardiac tissues (ECTs) in evaluation of nanoparticles toxicology, it remained necessary to understand the effects of IRONs on IDs assembly of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Western blotting showed increased expression of Cx43 in a dose-dependent manner, thus demonstrating the ability of IO-NPs in promoting gap junction assembly ( Figure 2B,E). As such, these results show how different functions were exerted by the IO-NPs when comparing a two-dimensional (2D) environment [65] with a three-dimensional (3D) environment [66].…”
Section: Cardioprotectionmentioning
confidence: 86%
See 1 more Smart Citation
“…Western blotting showed increased expression of Cx43 in a dose-dependent manner, thus demonstrating the ability of IO-NPs in promoting gap junction assembly ( Figure 2B,E). As such, these results show how different functions were exerted by the IO-NPs when comparing a two-dimensional (2D) environment [65] with a three-dimensional (3D) environment [66].…”
Section: Cardioprotectionmentioning
confidence: 86%
“…While the internalized IO-NPs showed in vitro peroxidase-like activity able to decrease the ROS levels, no changes in Cx43 expression could be observed (Figure 2A,D). However, the results were different in a follow-up study by the same group [66]. This time, the DMSA-coated IO-NPs were supplemented to primary cardiomyocytes seeded on a collagen/Matrigel scaffold ( Figure 2C).…”
Section: Cardioprotectionmentioning
confidence: 93%
“…Iron oxide nanoparticles also stimulate connexin 43 expression in order to promote co-culture of mesenchymal stem cells and cardiomyoblasts, resulting in increased therapeutic efficacy [104]. Mou et al had similar findings [105]. Thus, iron oxide nanoparticles do have a direct effect on cell signaling and phenotype.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 95%
“…By incorporating IONPs into bioengineered porous type I collagen patches to repair damaged myocardium, Mahmoudi et al developed a biodegradable material that could be imaged with MRI and also prevented the growth of Salmonella bacteria in the presence of the embedded NPs. In another work, it was shown that internalization of DMSA-IONPs by cardiac cells into collagen/Matrigel-based 3D engineered cardiac tissues increased biological activity and assembly of gap junctions, enhanced the assembly of electrochemical junctions and decreased adherens junctions and desmosomes [ 273 ].…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%